Climate Activism Favors Pro-environmental Consumption - Marco A. Marini; Samuel Nocito (Fondazione Eni Enrico Mattei (FEEM), 2023)
We investigate whether climate activism favors pro-environmental consumption by examining the impact of Fridays for Future (FFF) protests in Italy on second-hand automobile transactions in the strike-affected areas. Leveraging data on 10 million automobile transactions occurring before and after FFF, we exploit rainfall on the day of the events as exogenous source of attendance variation. Our findings reveal that local participation to the events is associated with a reduction in the per capita CO2 emissions of purchased cars, an uptick in the market share of low-emission vehicles and a corresponding decrease in the market share of high-emission counterparts. Notably, we uncover heterogeneous effects across gender and age groups. Results are primarily driven by a rise in the purchase of petrol cars, with electric cars contributing to a lesser extent, thereby displacing the demand for diesel vehicles. This evidence indicates substitution effects between goods prospectively subject to more stringent environmental regulations toward those obeying milder restrictions. The study provides valuable insights into the mechanisms underlying individuals' consumption choices under the influence of social protests.
Keywords: D12; D91; Q50; Q53; R41; 330; Fridays for Future; climate activism; green consumption; carbon emissions